ОДЗ x>0 (log²(2)x-2log(2)x)²+36log(2)x+45-18log²(2)x<0 (log²(2)x-2log(2)x)²-18(log²(2)x-2log(2)x)+45<0 log²(2)x-2log(2)x=a a²-18a+45<0 a1+a2=18 U a1*a2=45⇒a1=3 U a2=15 3<log²(2)x-2log(2)x<15 log(2)x=b 3<b²-2b<15 {b²-2b>3⇒b²-2b-3>0 {b²-2b<15⇒b²-2b-15<0 b1+b2=2 U b1*b2=-3⇒b1=-1 U b2=3 b<-1 U b>3 b3+b4=2 U b3*b4=-15⇒b3=-3 U b4=5 -3<b<5 -3<b<-1 U 3<b<5 -3<b<-1⇒-3<log(2)x<-1⇒1/8<x<1/2 3<b<5⇒3<log(2)x<5⇒8<x<32 ответ x∈(1/8;1/2) U (8;32)
ОДЗ x>0 (log²(2)x-2log(2)x)²+36log(2)x+45-18log²(2)x<0 (log²(2)x-2log(2)x)²-18(log²(2)x-2log(2)x)+45<0 log²(2)x-2log(2)x=a a²-18a+45<0 a1+a2=18 U a1*a2=45⇒a1=3 U a2=15 3<log²(2)x-2log(2)x<15 log(2)x=b 3<b²-2b<15 {b²-2b>3⇒b²-2b-3>0 {b²-2b<15⇒b²-2b-15<0 b1+b2=2 U b1*b2=-3⇒b1=-1 U b2=3 b<-1 U b>3 b3+b4=2 U b3*b4=-15⇒b3=-3 U b4=5 -3<b<5 -3<b<-1 U 3<b<5 -3<b<-1⇒-3<log(2)x<-1⇒1/8<x<1/2 3<b<5⇒3<log(2)x<5⇒8<x<32 ответ x∈(1/8;1/2) U (8;32)
2) 3/4+5/6=(9+10)/12=19/12
3) 2 3/4:11/10=11/4*10/11=10/4
4)19/12:3 1/6=19/12:19/6=19/12*6/19=1/2
5)10/4+1/2=(10+2)/4=12/4=3